2021
DOI: 10.1007/s00248-020-01666-8
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms of Pseudomonas and Lysinibacillus Marine Strains on High-Density Polyethylene

Abstract: Environmental pollution by plastic debris is estimated on a scale of 100 million metric tons, a portion of which is fragmented into micro-and nanoplastics. These fragments are often colonized by bacterial species in marine environments, possibly contributing to the biodegradation of such materials. However, further investigations are necessary to determine the impact of abiotic polymer weathering on biofilm adhesion, as well as the specific biofilm formation strategies employed by marine isolates. Here, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…As the biofilms developed (30 days), more living bacteria were observed together with the extracellular polymeric substances. This is consistent with the SEM images, indicating that these bacteria may devote part of their resources toward biofilm formation via production of extracellular polymeric substances, possibly at the cost of the colonization speed (Oliveira et al 2021).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As the biofilms developed (30 days), more living bacteria were observed together with the extracellular polymeric substances. This is consistent with the SEM images, indicating that these bacteria may devote part of their resources toward biofilm formation via production of extracellular polymeric substances, possibly at the cost of the colonization speed (Oliveira et al 2021).…”
Section: Resultssupporting
confidence: 89%
“…The presence of the blanket like extracellular polymeric substances on-top of the bacteria colonizing the surface of PE at day 10 (top left of Fig. 2) indicates that these bacteria may have utilized the PE as the carbon and energy source to drive the biofilm formation (Oliveira et al 2021). The SEM results showed that polymer components and the time for the interaction of MPs and colonizing microbes could synergistically affect the morphological characteristics of the biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…and Lysinibacillus sp. showed biofilm-related potential for high density PE biodegradation even within a short, 24 h test interval [ 80 ]. These microorganisms produced increased extracellular matrixes that improve cell adhesion to plastic surface.…”
Section: Psychrophilic Degradersmentioning
confidence: 99%
“…Microplastic pollution has reached nearly all ecosystems on the planet, including the seafloor (Kane et al, 2020). Microbial communities present in marine sediments interact with these plastic fragments, often colonizing their surface through the formation of biofilms (Lobelle & Cunliffe, 2011;Oliveira et al, 2021). A mature biofilm can impact physical properties of the colonized polymer, altering its crystallinity, molecular weight, hydrophobicity, surface morphology, and buoyance (Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The natural weathering of polymers in the environment, for instance, increases surface roughness and impacts biofilm formation. Our previous work has shown that the adhesion of marine bacteria to microplastics is impacted by surface weathering, to which bacteria respond by increasing the production of extracellular matrix (Oliveira et al, 2021). In this context, a similar characterization of marine yeast biofilms has not been addressed.…”
Section: Introductionmentioning
confidence: 99%